Galectin-9 Mediates HIV Transcription by Inducing TCR-Dependent ERK Signaling - Colomb, Florent; Giron, Leila B.; Premeaux, Thomas A.; Mitchell, Brooks I.; Niki, Toshiro; Papasavvas, Emmanouil; Montaner, Luis J.; Ndhlovu, Lishomwa C.; Abdel-Mohsen, Mohamed (Frontiers in Immunology, 2019)
Endogenous plasma levels of the immunomodulatory carbohydrate-binding protein galectin-9 (Gal-9) are elevated during HIV infection and remain elevated after antiretroviral therapy (ART) suppression. We recently reported that Gal-9 regulates HIV transcription and potently reactivates latent HIV. However, the signaling mechanisms underlying Gal-9-mediated viral transcription remain unclear. Given that galectins are known to modulate T cell receptor (TCR)-signaling, we hypothesized that Gal-9 modulates HIV transcriptional activity, at least in part, through inducing TCR signaling pathways. Gal-9 induced T cell receptor ζ chain (CD3ζ) phosphorylation (11.2% to 32.1%; P=0.008) in the J-Lat HIV latency model. Lck inhibition reduced Gal-9-mediated viral reactivation in the J-Lat HIV latency model (16.8% to 0.9%; P<0.0001) and reduced both Gal-9-mediated CD4+ T cell activation (10.3% to 1.65% CD69 and CD25 co-expression; P=0.0006) and IL-2/TNFα secretion (P<0.004) in primary CD4+ T cells from HIV-infected individuals on suppressive ART. Using phospho-kinase antibody arrays, we found that Gal-9 increased the phosphorylation of the TCR-downstream signaling molecules ERK1/2 (26.7 fold) and CREB (6.6 fold). ERK and CREB inhibitors significantly reduced Gal-9-mediated viral reactivation (16.8% to 2.6% or 12.6%, respectively; P<0.0007). Given that the immunosuppressive rapamycin uncouples HIV latency reversal from cytokine-associated toxicity, we also investigated whether rapamycin could uncouple Gal-9-mediated latency reactivation from its concurrent pro-inflammatory cytokine production. Rapamycin reduced Gal-9-mediated secretion of IL-2 (4.4-fold, P=0.001) and TNF (4-fold, P=0.02) without impacting viral reactivation (16.8% compared to 16.1%; P=0.2). In conclusion, Gal-9 modulates HIV transcription by activating the TCR-downstream ERK and CREB signaling pathways in an Lck-dependent manner. Our findings could have implications for understanding the role of endogenous galectin interactions in modulating TCR signaling and maintaining chronic immune activation during ART-suppressed HIV infection. In addition, uncoupling Gal-9-mediated viral reactivation from undesirable pro-inflammatory effects, using rapamycin, may increase the potential utility of recombinant Gal-9 within the reversal of HIV latency eradication framework.